TiO2 @ RGO (reduced graphene oxide) doped nanoparticles demonstrated improved photocatalytic activity. (31st May 2019) - Aqeel, M; Anjum, S; Imran, M; Ikram, M; Majeed, H; Naz, M; Ali, S; Ahmad, M A
Abstract: Reduced graphene oxide-RGO was employed in various concentrations (2, 4, 6, 8) % to TiO2 nanoparticles using colloidal blending. X-ray diffraction (XRD) confirmed presence of anatase phase and improved crystallinity with doping. The presence of functional groups and Ti–O–Ti (∼500–600 cm −1 ) were confirmed by Fourier transform infrared spectroscopy (FTIR). The absorption increased upon doping gradually recorded via UV–visible spectroscopy. The Graphene oxide-GO/RGO sheets and irregular spherical morphologies were observed under transmission and field emission electron microscope respectively. Raman spectrums confirmed GO in TiO2 and RGO-TiO2 nanocomposite showed highest photocatalytic potential with graphene oxide (8% wt/wt). The higher photocatalytic activity of nanocomposites is mainly due to reduced graphene oxide (RGO) acted as electron acceptor, adsorbent and photosensitizer in dyes photodecomposition. It is noteworthy that RGO-TiO2 is beneficial and promising photocatalyst to clean the environment and wastewater.